Efeito da estação do ano sobre a taxa de concepção e perda gestacional em vacas leiteiras mestiças - Ayres, Gustavo Ferreira (2012)
Bovines, as homeothermic animals, are able to keep their body temperature stable, but in tropical and subtropical regions, can suffer pronounced effects of heat stress because the high temperature and relative humidity. The objective was to evaluate the rate of conception and pregnancy loss during the seasons (winter and summer) in crossbred dairy cows. The experiment was conducted on the farm Glória of the Federal University of Uberlândia, Minas Gerais, Brazil. Was used a herd with average of 90 lactating cows, submitted to the IATF protocol, being inseminated or placed with a bull, totaling 370 inseminations from may/2007 to march/2010, which were divided for data analysis in three intervals, I, II and III, corresponding may/2007 to march/2008, april/2008 to march/2009, april/2009 to march/2010, respectively. The environment was characterized by average temperature, air humidity and ITU. After analyzing all the winters and summers, and the intervals I and II, there was a higher conception rate in winter than in summer. Already a pregnancy loss between 28 to 45 days after insemination, was not influenced by season of the year. We conclude that the region of Triângulo Mineiro, the warm season of the year negatively affects conception rate in crossbred dairy cows, but does not interfere in pregnancy loss between 28 to 45 days.